An active endoscope with small sweep volume that preserves image orientation for arthroscopic surgery - Ryu, Geunwoong; Kim, Jeongryul; Park, Chulmin; Kim, Keri (WILEY, 2021)
Background: Microsurgery is generally performed in narrow spaces with limited movement. Endoscopes that allow for angle changes have been developed using elastic materials, but they require a large bending space. We propose a new endoscope with a small sweep volume for angle changes. Methods: We fabricated a prototype with a thumb-operated joystick. The image sensor is attached to the tooltip. The image signal is input to a motor control board which computes inverse kinematics and transforms it into joint angle values. Each axis is positioned according to these values. Results: The tooltip sweeping volume was 104 mm(3). Surgeons at the Asan Medical Center used our endoscope to obtain images of the biceps tendon and subscapularis joints of a cadaver. Conclusion: Currently, a low-resolution image sensor is attached to endoscope tooltips. In the future, we will develop a high-resolution image module equipped with an ultra-small complementary metal oxide semiconductor sensor.
Keywords: SKULL BASE